Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species - Liu, Linjie; Li, Houhun (Zootaxa, 2016)
Ten species of the genus Parastenolechia Kanazawa, 1985 from Mainland China are reviewed. Six species are described as new: Parastenolechia arciformis sp. nov., P. papillaris sp. nov., P. trapezia sp. nov., P. semielliptica sp. nov., P. medispina sp. nov. and P. longifolia sp. nov. Parastenolechia albicapitella Park, 2000 is recorded for the first time in China. A key to the Parastenolechia species that occur in Mainland China is given.